Respostas

2014-05-19T12:15:47-03:00
Se, x/3 - 3 = 1/5 (2x + 2) - 4 ?


   x                 1
------ - 3 =    -------(2x +2) - 4
   3                 5

 x - 9              2x + 2
---------- =     -------------- - 4 
     3                   5                              mmc de (3; 5 ) = 3x5 = 15



5(x - 9) = 3(2x + 2) - 60
---------------------------------
              15

5(x - 9) = 3(2x + 2) - 60
5x - 45 = 6x + 6 - 60
5x - 6x- 45 = + 6 - 60
    - 1x - 45 = - 54
    - 1x =  - 54 + 45
    -1x = - 9 
 x = -9/-1
x = + 9 
              
1 5 1